Selection of Proteolytic Bacteria from Bonoloyo Public Burial Place (PBP), Banjarsari, Surakarta, Central Java - Putri Salwa Salsabilla; Yasir Sidiq; Erma Musbita Tyastuti; Triastuti Rahayu (Quagga: Jurnal Pendidikan dan Biologi, 2024)
Public Burial Place (PBP) is a cemetery for everyone. In PBP, protein decomposition occurs actively because the human body is made up of 16.4% protein, so it is most likely that proteolytic bacteria can be found. Previous research has isolated as many as 45 isolates from PBP Bonoloyo, Surakarta, but has not selected their proteolytic capabilities. The aim of the study was to isolate proteolytic bacteria from the Bonoloyo Public Cemetery and identify them. The bacterial isolate of PBP Bonoloyo is a collection from the FKIP Biological Laboratory of Muhammadiyah University of Surakarta that selected its proteolytic capabilities using the milk agar scheme (SMA). The parameters measured are the diameter of the colony and the lymphatic zone formed to obtain the value of the proteolytic index (IP). For bacterial isolates showing a positive proteolytic activity, simple identification is carried out through the observation of colonial morphology and Gramme colouring. The results of the study showed that as many as 28 isolates (62.2%) were positive for proteolytic activity, with IP values >2 for B1 and B3. Bacterial proteolytic isolates are dominantly white to yellow with irregular, filamentary, spindle, and circular colonial forms. The results of Gramme colouring show that bacterial isolates that have proteolytic abilities are a group of Gramme negative bacteria that are basil shaped. The bacterial isolate that shows the highest IP value is the B1 isolate, which is suspected to be of the genus Bacillus. This research obtained data showing that in the public cemetery (PBP), Bonoloyo stores potential as a proteolytic bacterial habitat for a group of Gramme negative bacteria.